Learning attitudes and satisfaction of college students toward health economics: a case study from a medical college in Guangxi province, China - Wu, Tengyan; Zhang, Xinhua; He, Lan; Feng, Qiming; He, Huimin (Frontiers in Education, 2025)
IntroductionIn China, the course of health economics in college is becoming increasingly important. It is very important to evaluate the learning attitude and feedback of college students in time to improve the teaching quality. However, there are few relevant studies. This study aims to understand the current situations of learning attitude and learning satisfaction about the course of health economics and its influencing factors based on the perspective of students, and put forward countermeasures and suggestions to improve the possible problems, to provide evidence-based reference for constantly improving the quality of teaching of health economics.MethodsIn this cross-sectional study, 354 students from a medical college in Guangxi were selected by the purpose sampling method, and online questionnaires were used to investigate the learning attitudes and satisfaction of college students about health economics. Descriptive and inferential statistical analyses of the collected data were carried out using IBM SPSS statistical software, with the aim of discussing how to optimize the teaching of health economics under the concept of student-centered evaluation in Chinese colleges, based on the findings.ResultsIt showed that students demonstrated higher learning enthusiasm and greater learning satisfaction. Chi-square test results showed a statistically significant difference in attitudes toward the “difficulty of learning” between students of different genders (x2 = 11.987, p = 0.002) and different birthplace (x2 = 8.750, p = 0.013). There was a statistically significant difference in attitudes toward “preview before class” among students from different majors (x2 = 14.929, p = 0.001). The Wilcoxon rank-sum test showed statistically significant differences in overall satisfaction scores based on genders, birthplaces, majors, and learning attitudes (p < 0.05).DiscussionTo improve the teaching effectiveness of the course, greater attention should be given to female students, those from rural areas, and public health majors. The course should adopt a student-centered teaching design that cultivates students’ability to independent learning, thinking, and expression.